"Even if you're HIV-positive there's life after if you take your medication": experiences of people on long-term ART in South Africa: a short report. Issue 8 (3rd August 2019) - Hendrickson, C.; Moolla, A.; Maskew, M.; Long, L.; Fox, M. P.; Sanne, I.; Majuba, P.; Pascoe, S.
ABSTRACT: South Africa's national antiretroviral treatment (ART) programme, initiated in 2004, is the largest HIV treatment programme in the world with an estimated 4.2 million people on ART. Today, an HIV diagnosis is no longer associated with certain death, but is rather a manageable chronic disease, with all HIV-positive patients now eligible to receive treatment. In this study, we explore patient experiences at the onset of the ART programme, including facilitators and barriers around decision-making along the HIV care cascade (HIV testing, ART initiation, retention, and adherence). We conducted twenty-four in-depth interviews among adults (≥18 years old) who initiated ART between April 2004 and March 2005 and were alive, on treatment at enrolment (October 2015–March 2016) at a large public-sector clinic in Johannesburg, South Africa. Data were analysed using a thematic analysis approach. Patients cited physical wellbeing, responsibility for raising children, supportive clinic staff and noticeable improvements in health on ART as key facilitators to continued care. In contrast, changing clinic conditions, fear of side-effects and stigma were mentioned as barriers. This study provides a unique lens through which to evaluate factors associated with long-term retention and adherence to ART at a crucial time in ART programming when more people will be initiating life-long treatment. We must continue to focus on supportive and empathetic clinic environments, more convenient ways to access medication for patients, and developing tools or interventions that continue to address the issues of stigma and discrimination and build the support networks for all those on treatment.